The very best of the best : 35 years of the Year's Best Science Fiction - Dozois, Gardner R (St. Martin's Griffin, 2019)
"For the first time in a decade, a compilation of the very best in science fiction, from a world authority on the genre. For decades, the Year's Best Science Fiction has been the most widely read short science fiction anthology of its kind. Now, after thirty-five annual collections. comes the ultimate in science fiction anthologies. In The Very Best of the Best, legendary editor Gardner Dozois selects the finest short stories for this landmark collection."--Publisher's description.